P390 Ustekinumab modulates IL-12 and IL-23-related cell type-specific inflammatory transcriptional states in Ulcerative Colitis induction therapy. (30th January 2023) - Richards, D; Venkat, S; Freeman, T C; Mcrae, B; Hoops, T; Marano, C; Branigan, P
Abstract: Background: Ustekinumab (UST) is a monoclonal antibody specific for the p40 subunit of interleukin (IL)-12 and IL-23. In a randomised phase 3 trial (UNIFI; NCT02407236) in patients with moderate-to-severe ulcerative colitis (UC), UST was shown to be more effective for inducing and maintaining clinical remission than placebo. There has yet to be a mechanistic understanding of p40 blockade in inflammatory bowel disease. Here, we investigated the underlying molecular mechanism of action of UST in UC. Methods: Paired colon biopsies for transcriptomic analysis were obtained at screening and week 8 in patients who received a single intravenous induction treatment of placebo (n=145 subjects), UST 130 mg (n=155 subjects), or a weight-range-based dose (approximated to UST 6 mg/kg of body weight; n=171 subjects). Tissue transcriptional profiles were determined using Affymetrix microarrays. Transcriptional changes were analysed in the context of cell type-specific co-expression modules derived from single cell UC data. Gene set variation analysis (GSVA) was used to quantitatively assess changes in specific biologic modules in the context of endoscopic and histologic-endoscopic mucosal improvement (HEMI) responder and non-responder analyses. Nichenet, which predicts ligand–target gene links, was used with single cell UC data to identify ligands that are predicted to be associated with our cell type-specific modules. Results: By week 8, both UST treatment arms induced a greater magnitude of transcriptional changes associated with Th17, Th1 cytotoxicity, myeloid inflammatory, epithelial inflammatory, and inflammatory fibroblast modules compared with placebo. Ligand-target gene predictions indicate IL-12 and IL-23 are associated with changes in the Th1 cytotoxicity and Th17 module expression, respectively. Population level molecular changes in both UST treatment arms are consistent with endoscopic and HEMI response at week 8. When evaluating sub-groups stratified by endoscopic improvement or HEMI status, significant changes were observed in transcriptional modules in both UST responders and UST non-responders identifying mechanistic processes associated with dual blockade of IL-12 and IL-23 following exposure to UST. Placebo non-responders showed no significant changes. Conclusion: Molecular analysis of colon biopsies from UC patients after UST induction revealed IL-12 and IL-23-related transcriptional changes associated with Th1 cytotoxicity and Th17 biology. By leveraging UC single cell derived transcriptional modules, we have identified key disease-relevant processes that significantly changed with UST treatment, regardless of response status and have extended the mechanistic understanding of p40 blockade in UC.